Opportunities and challenges for electronic health record: concepts, costs, benefits, and regulation - Jacquinet, Marc (2016)
In this section, after a brief history, the issue of definition and several dimensions of electronic health records will be tackled. If the first known medical records can be traced to Hippocrates and the goals he attributed to these records were to describe accurately the course of a disease and gives a probable cause of it; the electronic dimension of these records can be traced back to the 1960s in some hospitals that started a more systematic recording and use of patients’ data by services and doctors. But it is still more recently, in the 1990s, with the ever wider use of internet and online databases that the electronic health record emerged as a new tool in the public health systems of OECD countries. There are different definitions of electronic health record, depending on the theoretical perspective or even the main user or the political point of departure taken in the implementation process. Even so, here and in the literature on the subject, the electronic health record has become and is the generic term. Other focuses like electronic medical record (or registry) and the electronic patient record are based on either the perspective of the user or the subject of the information. All these expressions are part of the general move from traditional management of health and medicine to electronic health and medicine or e-health (written more and more frequently ehealth as its use spreads across countries and within national health and health care systems). To settle the record straight, the definition of the Electronic Health Record that can serve as a consensus for the current exposition as well as a starting point for further research is the one given by the International Standards Organization